INNOVATIONS IN THE ANCIENT COMMUNICATION NETWORK - Novozhenov; Baipakov; Savelieva; Sydykov (Revista Inclusiones, 2020)
The focus of the present study is on the role of innovation in the communication network of earliest Bronze Age population of Eurasia steppes, when trans-continental global World-System was created. Certain innovations of that period were distributed in the territory of continental steppes and thus formated the historical development of the local clans and the Bronze Age societies. Along with logistics (import and exchange of goods) which is material evidence of allocated archaeological cultures (AC); there was a spread of ‘transcultural’ innovations - new technologies, ideas, images, signs, their combinations and codes, and mythology, expressed in certain cultural, pictorial, funeral, megalithic traditions, rituals, the carriers of which were individual mobile clans of cattle breeders. These ‘transcultural’ innovations and traditions can be considered indicators or markers of the unique identity of a society or clan. Such ‘transcultural’, traditional, irrational features in the steppe AC are probably closest to the ethnic basis of ancient societies.